A mega-analysis of memory reports from eight peer-reviewed false memory implantation studies. Issue 2 (7th February 2017) - Scoboria, Alan; Wade, Kimberley A.; Lindsay, D. Stephen; Azad, Tanjeem; Strange, Deryn; Ost, James; Hyman, Ira E.
ABSTRACT: Understanding that suggestive practices can promote false beliefs and false memories for childhood events is important in many settings (e.g., psychotherapeutic, medical, and legal). The generalisability of findings from memory implantation studies has been questioned due to variability in estimates across studies. Such variability is partly due to false memories having been operationalised differently across studies and to differences in memory induction techniques. We explored ways of defining false memory based on memory science and developed a reliable coding system that we applied to reports from eight published implantation studies ( N   =  423). Independent raters coded transcripts using seven criteria: accepting the suggestion, elaboration beyond the suggestion, imagery, coherence, emotion, memory statements, and not rejecting the suggestion. Using this scheme, 30.4% of cases were classified as false memories and another 23% were classified as having accepted the event to some degree. When the suggestion included self-relevant information, an imagination procedure, and was not accompanied by a photo depicting the event, the memory formation rate was 46.1%. Our research demonstrates a useful procedure for systematically combining data that are not amenable to meta-analysis, and provides the most valid estimate of false memory formation and associated moderating factors within the implantation literature to date.